Implementation of an oral dialogue based on a neural network of artificial intelligence in the online platform in secondary school - Karauylbayev, Sapargali; Zhumabaeva, Aizhamal; Kalymbet, Aibek (Pedagogy and Psychology, 2021)
Today in society there is a need for artificial intelligence that teaches schoolchildren through oral communication, questions and answers. In the first quarter of the 2020-2021 academic year, secondary school teachers in Kazakhstan spent more time checking students’ written responses compared to traditional teaching in previous years. At this time, the teachers noted that there was not enough time to verbally explain the lessons and provide high-quality oral feedback to all students. To solve this problem, we propose to use an artificial intelligence neural network to verbally explain the topic of the lesson in an online learning platform. The proposed article analyses and investigates the methodology for the implementation of oral teaching of schoolchildren using artificial intelligence neural networks in online learning in general education schools. The neural network recognises a school textbook and processes it in a text and audio editor. oral explanation to the student of the theoretical material from the textbook alternates with the assessment of the student’s voice response. An online demonstration of ways to solve programming problems is carried out in an online editor installed on an online platform. The proposed online platform can be effectively used in traditional face-to-face education.